2011
DOI: 10.1159/000322560
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Inflammatory Responses in Large and Small Airways in Smokers with and without Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterised by progressive and irreversible airway obstruction. Smoking causes persistent inflammation in lung tissue. However, differences in inflammatory responses between the large and small airways have not been systematically explored among smokers with and without COPD. Objectives: The aim of our research was to characterise the expression and localisation of NF-ĸBp65 and histone deacetylase 2 (HDAC2) as well as inflammatory cell (macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 50 publications
6
29
0
Order By: Relevance
“…In accordance with previous studies [30,31,32,33], we observed a higher density of alveolar CD8+ cells and macrophages in COPD patients. Few studies have investigated the relationship between inflammation and AHR in COPD.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies [30,31,32,33], we observed a higher density of alveolar CD8+ cells and macrophages in COPD patients. Few studies have investigated the relationship between inflammation and AHR in COPD.…”
Section: Discussionsupporting
confidence: 93%
“…As oxidative stress is highly related with the progression and consequently with the exacerbations of this disease, the use of antioxidants is likely to have a beneficial outcome [12]. The antioxidant agent N-acetyl- L -cysteine (NAC) inhibits oxidative stress changing the cellular redox status and acting as a direct reactive oxygen species (ROS) scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…There is convincing evidence that neutrophils are one of the primary effector cells in COPD [3,4,5,6,7]. The number of neutrophils is increased in bronchoalveolar lavage fluid as well as in induced sputum samples and airways from COPD patients [6,8,9]. The amount of neutrophils correlates with disease severity and progression in these patients [3,8].…”
Section: Introductionmentioning
confidence: 99%